5問 掛け算・割り算 分数掛け算・割り算 数学・算数の教材公開ページ

20 

Loading....

Loading....

Loading....

Loading....

Loading....

全文

(1)

(1) 32 ÷ 5

6 = (2)

1

6 ×3 =

(3) 74 ÷ 3

2 = (4)

1 6 ÷

1 3 =

(5) 16 × 3 4 =

(2)

(1) 32 ÷ 5 6 =

9

5

(2)

1

6 ×3 =

1

2

(3) 74 ÷ 3 2 =

7

6

(4)

1 6 ÷

1 3 =

1

2

(5) 16 × 3 4 =

1

8

(3)

(1) 23 × 1

6 = (2)

6 5 ×

4 3 =

(3) 53 ÷ 5

6 = (4)

5 6 ÷

5 3 =

(5) 6× 1 3 =

(4)

(1) 23 × 1 6 =

1

9

(2)

6 5 ×

4 3 =

8

5

(3) 53 ÷ 5

6 =

2

(4) 5

6 ÷ 5 3 =

1

2

(5) 6× 1

3 =

2

(5)

(1) 56 ÷ 4

3 = (2)

5 6 ÷

1 3 =

(3) 16 ÷ 1

3 = (4)

1 6 ×

3 4 =

(5) 56 × 3 4 =

(6)

(1) 56 ÷ 4 3 =

5

8

(2)

5 6 ÷

1 3 =

5

2

(3) 16 ÷ 1 3 =

1

2

(4)

1 6 ×

3 4 =

1

8

(5) 56 × 3 4 =

5

8

(7)

(1) 65 × 5

4 = (2)

4 5 ×

1 2 =

(3) 56 ÷ 4

3 = (4)

3 2 ÷

1 6 =

(5) 34 × 1 6 =

(8)

(1) 65 × 5 4 =

3

2

(2)

4 5 ×

1 2 =

2

5

(3) 56 ÷ 4 3 =

5

8

(4) 32 ÷ 1

6 =

9

(5) 34 × 1 6 =

1

8

(9)

(1) 16 × 3

4 = (2)

3 4 ÷

5 6 =

(3) 16 ÷ 4

3 = (4)

5 6 ÷

5 3 =

(5) 6× 4 3 =

(10)

(1) 16 × 3 4 =

1

8

(2)

3 4 ÷

5 6 =

9

10

(3) 16 ÷ 4 3 =

1

8

(4)

5 6 ÷

5 3 =

1

2

(5) 6× 4

3 =

8

(11)

(1) 12 ÷ 1

6 = (2)

5 6 ÷

5 3 =

(3) 52 ÷ 7

4 = (4)

1 6 ÷

2 3 =

(5) 2× 5 4 =

(12)

(1) 12 ÷ 1

6 =

3

(2) 5

6 ÷ 5 3 =

1

2

(3) 52 ÷ 7 4 =

10

7

(4)

1 6 ÷

2 3 =

1

4

(5) 2× 5 4 =

5

2

(13)

(1) 56 ÷ 1

3 = (2) 6×

1 4 =

(3) 34 × 5

6 = (4)

1 6 ÷

1 3 =

(5) 65 × 5 3 =

(14)

(1) 56 ÷ 1 3 =

5

2

(2) 6

× 1 4 =

3

2

(3) 34 × 5 6 =

5

8

(4)

1 6 ÷

1 3 =

1

2

(5) 65 × 5

3 =

2

(15)

(1) 56 ÷ 1

3 = (2)

3 4 ÷

5 6 =

(3) 14 ÷ 1

6 = (4)

5 6 ×

2 5 =

(5) 65 × 5 3 =

(16)

(1) 56 ÷ 1 3 =

5

2

(2)

3 4 ÷

5 6 =

9

10

(3) 14 ÷ 1 6 =

3

2

(4)

5 6 ×

2 5 =

1

3

(5) 65 × 5

3 =

2

(17)

(1) 12 ÷ 1

4 = (2)

3

4 ×6 =

(3) 53 ÷ 1

6 = (4)

3 5 ×

1 6 =

(5) 34 ÷ 1 6 =

(18)

(1) 12 ÷ 1

4 =

2

(2) 3

4 ×6 =

9

2

(3) 53 ÷ 1

6 =

10

(4) 3

5 × 1 6 =

1

10

(5) 34 ÷ 1 6 =

9

2

(19)

(1) 43 × 5

6 = (2)

5 6 ×

3 4 =

(3) 6× 1

4 = (4)

5 6 ÷

3 2 =

(5) 52 × 6 5 =

(20)

(1) 43 × 5 6 =

10

9

(2)

5 6 ×

3 4 =

5

8

(3) 6× 1 4 =

3

2

(4)

5 6 ÷

3 2 =

5

9

(5) 52 × 6

5 =

3

Updating...

参照

Updating...

関連した話題 :